Performance of All-Solid-State MoOx pH Sensors Prepared via Thermal Oxidation for Robust Applications - Djouhar Aoubida; Stephanie Betelu; Johan Bertrand; Quoc Nghi Pham; Diana Dragoe; Nita Dragoe; Ioannis Ignatiadis (Sensors)
In this study, we investigated the morphology, chemical composition and pH measurement performance of MoOx electrodes prepared via thermal oxidation and submitted to hydration in milliQ water. Surface analysis using SEM-EDS and XPS revealed that the hydrated MoOx film is composed of different oxidation states of Mo (Mo (IV), Mo (V) and Mo (VI)), influencing its electrochemical behavior. A hydration period of 45 days was required for the electrode to achieve a response approaching the Nernstian model (−58 mV/pH), while extended hydration of up to 70 days enhanced its stability and sensitivity. The electrode’s performance was assessed under various conditions, including in the presence and absence of oxygen and in anaerobic conditions with the presence of sulfides. Oxygen absence increased sensitivity and lowered the experimental standard potential (E0Exp) due to the effect of oxygen vacancies. Low sulfide concentrations had minimal impact on electrode performance, although higher concentrations may slightly decrease the electron transfer efficiency due to the complex formation. The pH sensing mechanisms of MoOx electrodes are also discussed.